Complex Polypropionates from a South China Sea Photosynthetic Mollusk: Isolation and Biomimetic Synthesis Highlighting Novel Rearrangements - Wu, Qihao; Li, Song‐Wei; Xu, Heng; Wang, Hong; Hu, Pei; Zhang, Hao; Luo, Cheng; Chen, Kai‐Xian; Nay, Bastien; Guo, Yue‐Wei; Li, Xu‐Wen (Angewandte Chemie International Edition, 2020)
Placobranchus ocellatus is well known to produce diverse and complex γ‐pyrone polypropionates. In this study, the chemical investigation of P. ocellatus from the South China Sea led to the discovery and identification of ocellatusones A–D, a series of racemic non‐γ‐pyrone polyketides with novel skeletons, characterized by a bicyclo[3.2.1]octane (1, 2), a bicyclo[3.3.1]nonane (3) or a mesitylene‐substituted dimethylfuran‐3(2H)‐one core (4). Extensive spectroscopic analysis, quantum chemical computation, chemical synthesis, and/or X‐ray diffraction analysis were used to determine the structure and absolute configuration of the new compounds, including each enantiomer of racemic compounds 1–4 after chiral HPLC resolution. An array of new and diversity‐generating rearrangements is proposed to explain the biosynthesis of these unusual compounds based on careful structural analysis and comparison with six known co‐occurring γ‐pyrones (5–10). Furthermore, the successful biomimetic semisynthesis of ocellatusone A (1) confirmed the proposed rearrangement through an unprecedented acid induced cascade reaction. A series of racemic polypropionates with novel polycyclic skeletons were discovered and structurally elucidated from the South China Sea photosynthetic sacoglossan mollusk Placobranchus ocellatus. An array of new and diversity‐generating rearrangements is proposed to explain the biosynthesis of these unusual compounds. Furthermore, the successful biomimetic semisynthesis of ocellatusone A confirmed the proposed rearrangement through an unprecedented acid induced cascade reaction.